The Importance of Entrepreneurship Learning in University: An Empirical Research - Turku, Dhurata (European Journal of Economics and Business Studies, 2016)
After finishing the university, students usually do not know what to do. Most of them cannot find a job. Based on our mentality, working is considered by the student an employment with a salary, mainly in public sector or in private sector based on the diploma university. If this does not function, the graduated student calls him/herself unemployed and does not hope for his future. Salary employment is not and cannot be the only solution in everyone’s life. If a student is graduated and cannot find a job based on a salary, he/she may use his/her abilities about entrepreneurship that he/she has learnt at university. To be self-employed does not need the condition o having a diploma in economic studies. Everyone that has a diploma and who does not have a job based on a salary, may be a successful self-employed. A very important role is the entrepreneurship learning during studies. Such an education would be necessary for all the students in all university branches. To know how much our students know about entrepreneurship and which are their needs in relation to the entrepreneurship, there are analyzed and concluded questionnaires and interviews with 283 students of Education Sciences in “Aleksandër Xhuvani” University, Elbasan.